High-refractive-index wear-resistant optical coating and preparation method thereof
By using ordinary polyurethane acrylate prepolymers, nano-inorganic substances and modified wear-resistant inorganic substances in optical coatings, the problem of insufficient wear resistance of existing high-refractive index coatings is solved, the effect of high refractive index and wear resistance is achieved, and the flexible design of refractive index is provided.
Patent Information
- Application Number
- CN202411607850.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
AI Technical Summary
While increasing the refractive index, existing high-index optical coatings are difficult to take into account both wear resistance, and the refractive index of commonly used high-index resins is fixed, making it difficult to design freely within a certain range.
Ordinary polyurethane acrylate prepolymer is used to combine high-refractive index nanoinorganic substances and modified wear-resistant inorganic substances. By reacting the surface reactive groups of the modified wear-resistant inorganic substances with the polymer, the wear resistance of the coating is improved, and the refractive index is adjusted through nanofillers.
The effect of high refractive index and wear resistance is achieved, the limitation of using high refractive index resin is avoided, and the refractive index can be freely designed within a certain range, which is suitable for a variety of optical applications.
Smart Images

Figure BDA0005130101720000091 
Figure BDA0005130101720000101 
Figure BDA0005130101720000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical coatings, and in particular to a high-refractive-index wear-resistant optical coating and a preparation method thereof. Background Art
[0002] Because some electrical equipment, such as lenses and OLED lighting, have certain requirements for the refractive index of the optical elements contained therein, and if the production technicians want to obtain a higher refractive index of the optical element, they usually increase the curvature and thickness of the optical element. However, blindly increasing the thickness of the optical element is not conducive to the lightweight and miniaturization of the electronic equipment, and increasing the curvature leads to a significant increase in the difficulty and cost of preparing the optical element. Therefore, in order to obtain the required refractive index without excessively increasing the curvature and thickness of the optical element, the prior art basically achieves this by coating a high refractive index optical coating on the surface of the optical element. Currently available high refractive index coatings are usually prepared using high refractive index resins as raw materials, and the refractive index of high refractive index resins is a fixed value, and the functionality is generally not high, resulting in low hardness. Summary of the invention
[0003] The purpose of the present invention is to provide a high refractive index wear-resistant optical coating and a preparation method thereof in view of the deficiencies in the prior art. The coating adopts ordinary polyurethane acrylate prepolymer with high refractive index nano-inorganic matter and modified wear-resistant inorganic matter to achieve the effects of high refractive index and wear resistance; the wear-resistant inorganic matter is modified so that its surface has reactive groups that can react with the polymer, thereby improving the wear resistance; compared with the commonly used high refractive index coating, there is no need to use high refractive index resin as a raw material, the refractive index is adjusted by nano fillers, and can be freely designed within a certain range.
[0004] In order to achieve the above object, the present invention adopts the following technical solution.
[0005] A high-refractive-index wear-resistant optical coating, the components of which are calculated by weight percentage: 40-65% UV oligomer, 15-40% high-refractive-index nano inorganic matter, 1-5% modified wear-resistant inorganic matter, 0-5% high water drop angle additive, and 1-6% photoinitiator.
[0006] Furthermore, the UV oligomer includes one or a mixture of urethane acrylate oligomer, epoxy acrylate oligomer, polyester acrylate oligomer, epoxy glycidyl ether oligomer, and epoxy cyclohexane oligomer; preferably, oligomers with three or more functional groups have better scratch resistance, and more preferably, oligomers with five or more functional groups have better hardness and scratch resistance; the UV oligomer accounts for 40 to 65% of the total solid weight ratio.
[0007] Furthermore, the high-refractive index nano inorganic material comprises one or a mixture of nano titanium dioxide, nano silicon nitride, nano aluminum nitride, nano zirconium oxide, nano silicon carbide, nano niobium pentoxide, and nano gallium nitride. The refractive index of the high-refractive index nano inorganic material is above 2.0, and the particle size is between 5 and 200 nm; the preferred particle size is between 5 and 100 nm, at which time the transparency effect of the high-refractive index wear-resistant coating is optimal and the haze is lowest; when the particle size is greater than 100 nm, the haze of the coating will exceed 2.0%, which cannot meet the requirements of the optical application field; when selecting the high-refractive index nano inorganic material, it is preferred to use a material with a white or light-colored appearance to reduce the absorption of visible light by the inorganic material and prevent the appearance of the coating from looking colored after application.
[0008] Furthermore, the high-refractive-index nano-inorganic material accounts for 15-40% of the total solid weight ratio, preferably between 25-35%; when the proportion of the high-refractive-index nano-inorganic material exceeds 40%, the high-refractive-index nano-inorganic material is insufficiently wrapped by the prepolymer, resulting in decreased adhesion and too high haze of the coating; when the proportion of the high-refractive-index nano-inorganic material is less than 15%, the refractive index of the coating is not significantly improved, and the requirements for the application of high-refractive-index coatings cannot be met.
[0009] The present application can adjust the refractive index of the coating by adjusting the proportion of the high-refractive nano-inorganic material. The higher the proportion of the high-refractive nano-inorganic material, the higher the refractive index of the coating.
[0010] Furthermore, the modified wear-resistant inorganic material includes a mixture of one or more of aluminum oxide, zirconium oxide, boron carbide, silicon carbide, silicon nitride, aluminum nitride, and titanium carbide; the Mohs hardness of the modified wear-resistant inorganic material is greater than 8.0; the shape of the modified wear-resistant inorganic material is spherical or quasi-spherical; the modified wear-resistant inorganic material accounts for 1 to 5% of the total solid weight ratio; when the modified wear-resistant inorganic material accounts for more than 5%, the haze of the coating will increase; when the modified wear-resistant inorganic material accounts for less than 1%, the modified wear-resistant inorganic material cannot provide scratch resistance to the coating.
[0011] Specifically, the modified wear-resistant inorganic material preferably has a particle size between 30 and 200 nm, and the particle size needs to be 50 to 150% of the coating thickness. More preferably, an inorganic oxide with a particle size between 50 and 150 nm is selected, and the scratch resistance is better at this time. The thickness of the high-refractive coating can be determined by optical simulation software according to the specific product application requirements.
[0012] Furthermore, the modification process of the modified wear-resistant inorganic material is selected according to the type of UV oligomer selected. When a UV oligomer containing double bonds is selected, a vinyl-modified wear-resistant inorganic material is selected; when a UV oligomer containing epoxy groups is selected, an epoxy-modified wear-resistant inorganic material is selected.
[0013] Specifically, the modification method of the vinyl-modified wear-resistant inorganic material is as follows: one or more modifiers selected from vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tripropoxysilane, and vinyl tri(β-methoxyethoxy)silane are added to organic solvents such as ethyl acetate, butyl acetate, ethanol, and butanone and the wear-resistant inorganic material, the wear-resistant inorganic material and the organic solvent are mixed in a ratio of 2:8, and after mixing evenly, 0.5-5% of the modifier is added to the mixed solution, the solution is kept at 40-70° C. for reaction for 1-3 hours, and after the reaction is completed, the solvent in the solution is baked and volatilized to obtain the vinyl-modified wear-resistant inorganic material;
[0014] Specifically, the modification method of the epoxy-modified wear-resistant inorganic material is as follows: one or more modifiers selected from γ-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are added to organic solvents such as ethyl acetate, butyl acetate, ethanol, and butanone and the wear-resistant inorganic material, and the wear-resistant inorganic material and the organic solvent are mixed in a ratio of 2:8. After the mixture is evenly mixed, 0.5-5% of the modifier is added to the mixed solution, and the solution is kept at 40-70°C for reaction for 1-3 hours. After the reaction is completed, the solvent in the solution is baked and evaporated to obtain the epoxy-modified wear-resistant inorganic material.
[0015] Furthermore, the high water drop angle additive includes one or a mixture of fluorine-modified acrylate, fluorine-silicon-modified acrylate, and silicone-modified acrylate, and the high water drop angle additive contains a reactive group that reacts with UV oligomers; these include Japanese DIC RS-90, Japanese Shin-Etsu KY-1203, Tianze New Materials 109AF, etc.; the fluorine / silicon compound makes the surface of the coating flat and smooth, and further improves the wear resistance of the coating.
[0016] Furthermore, the high water drop angle additive accounts for 0-5% of the total solid weight ratio. Whether to add the high water drop angle additive depends on whether the high fold wear-resistant coating is the outermost layer, that is, whether it needs to be re-coated. When the high fold wear-resistant coating is the outermost layer, the wear resistance can be improved by adding the high water drop angle additive. At this time, the proportion of the high water drop angle additive is between 1% and 5%. When it is lower than 1%, the scratch resistance will be reduced. When it is higher than 5%, the compatibility of the coating will deteriorate, which will affect the transparency. In addition, this type of additive is generally more expensive, and too high a proportion will greatly increase the cost. When the high fold wear-resistant coating is not the outermost layer, the high water drop angle additive cannot be added to avoid affecting the construction of the outer coating.
[0017] Furthermore, the photoinitiator includes one or a mixture of a free radical photoinitiator and a cationic photoinitiator, and the free radical initiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1,1'-(methylenedi-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (127), 2-methyl-1-[4-(methylthio)phenyl ]-2-(4-morpholinyl)-1-propanone (907), tetraethyl Michler's ketone (MEK); the cationic photoinitiator includes bis(4-dodecylbenzene)iodonium hexafluoroantimonate (PAG-101), diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate (6976), diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (6992), 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate (6990), and 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate (250).
[0018] Furthermore, the amount of photoinitiator used is 1-6% of the total solids, wherein the amount of free radical photoinitiator preferably accounts for 3-5% by weight of the total solids, and the amount of cationic photoinitiator preferably accounts for 1-3% by weight of the total solids; if the initiator ratio is too low, the coating will not be completely cured, affecting the hardness and scratch resistance of the coating; if the initiator ratio is too high, the coating will be excessively cross-linked, resulting in a decrease in the adhesion performance of the coating, yellowing of the coating and other defects.
[0019] It should be noted that in the above technical solution, in specific applications, the pencil hardness of the hardened layer itself needs to be above H, preferably above 3H, and the hardened layer should not be completely cured during curing, leaving a part of the reactive groups to cross-link with the reactive groups in the high refractive index wear-resistant coating, which can greatly improve the adhesion and wear resistance. The thickness of the hardened layer is between 1 and 50 μm, and the adhesion between the hardened layer and the substrate and the coating of the present invention needs to reach 4B or above in the 100-grid test.
[0020] In order to enable those skilled in the art to more conveniently obtain the high refractive index wear-resistant optical coating provided by the present invention, on the basis of the above technical solution, the present invention also provides a method for preparing the high refractive index wear-resistant optical coating, comprising the following steps:
[0021] Step 1: Add a sufficient amount of UV oligomer into a stirring barrel, and then place the stirring barrel in a stirrer for stirring, with the speed set at 800-1000 rad / min;
[0022] Step 2, add a sufficient amount of high-refractive nano inorganic material while stirring, after the addition is completed, set the stirrer to 1200-1500 rad / min and stir for 30 minutes;
[0023] Step 3, then add a sufficient amount of modified wear-resistant inorganic material while stirring, after the addition is completed, set the mixer to 1200-1500 rad / min and stir for 30 minutes;
[0024] Step 4: Grind and disperse the above-mixed product using a sand mill or a three-roll grinder, and pour the ground product into a mixing barrel and stir at 800-1000 rad / min;
[0025] Step 5, dilute the high water drop angle additive by 10 times with an organic solvent such as ethyl acetate or butanone (it is less likely to cause shrinkage abnormalities when the water drop angle additive is diluted), and then add it to the mixing bucket while stirring. After the addition is completed, set the mixer to 1200-1500 rad / min and stir for 30 minutes;
[0026] Step 6: Add a sufficient amount of photoinitiator to the mixing bucket. After adding, the coating needs to be covered with a bucket cover to avoid light. Set the mixer to 1200-1500 rad / min and stir for 10 minutes.
[0027] Step 7: The stirred coating is filtered using a 0.5-1 μm filter element to obtain a high-refractive, wear-resistant optical coating.
[0028] During construction, add sufficient amount of organic solvents such as ethyl acetate, butyl acetate, butanone, methyl isobutyl ketone, etc. to dilute according to specific construction requirements.
[0029] Compared with the prior art, the advantages and positive effects of the present invention are:
[0030] 1. The high refractive index wear-resistant optical coating provided by the present invention adopts ordinary polyurethane acrylate prepolymer with high refractive index nano-inorganic material and modified wear-resistant inorganic material to achieve the effects of high refractive index and wear resistance; by modifying the wear-resistant inorganic material so that its surface has reactive groups that can react with the polymer, the wear resistance can be improved; compared with the commonly used high refractive index coating, there is no need to use high refractive index resin as raw material, the refractive index is adjusted by nano filler, and can be freely designed within a certain range.
[0031] 2. The high-refractive-index wear-resistant optical coating provided by the present invention can be applied to the anti-peep film of the display screen of mobile phones and tablet computers, and can also be applied to the high-fold layer material in the multi-layer anti-reflective material with high and low fold layers. For example, the anti-reflective film in the folding mobile phone is a structure using a combination of high and low fold layers; the multi-layer anti-reflective material can achieve a lower reflectivity than a single-layer low-fold layer by alternating the high and low fold layers according to the thickness designed by the optical software, and the high-refractive-index material is indispensable. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solutions in this specification, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0033] Example
[0034] The invention discloses a high-refractive-index wear-resistant optical coating, wherein the components of the high-refractive-index wear-resistant optical coating are as follows by weight percentage: 40-65% of UV oligomer, 15-40% of high-refractive-index nano inorganic matter, 1-5% of modified wear-resistant inorganic matter, 0-5% of high water drop angle auxiliary agent, and 1-6% of photoinitiator.
[0035] Furthermore, the UV oligomer includes one or a mixture of urethane acrylate oligomer, epoxy acrylate oligomer, polyester acrylate oligomer, epoxy glycidyl ether oligomer, and epoxy cyclohexane oligomer.
[0036] Furthermore, the high-refractive-index nano-inorganic material includes one or a mixture of nano-titanium dioxide, nano-silicon nitride, nano-aluminum nitride, nano-zirconium oxide, nano-silicon carbide, nano-niobium pentoxide, and nano-gallium nitride. The high-refractive-index nano-inorganic material has a refractive index of more than 2.0 and a particle size of 5 to 100 nm.
[0037] Furthermore, the modified wear-resistant inorganic material includes a mixture of one or more of aluminum oxide, zirconium oxide, boron carbide, silicon carbide, silicon nitride, aluminum nitride, and titanium carbide. The Mohs hardness of the modified wear-resistant inorganic material is greater than 8.0, and the shape of the modified wear-resistant inorganic material is spherical or quasi-spherical.
[0038] Furthermore, the modification process of the modified wear-resistant inorganic material is selected according to the type of UV oligomer selected. When a UV oligomer containing double bonds is selected, a vinyl-modified wear-resistant inorganic material is selected; when a UV oligomer containing epoxy groups is selected, an epoxy-modified wear-resistant inorganic material is selected.
[0039] Specifically, the modification method of the vinyl-modified wear-resistant inorganic material is as follows: one or more modifiers selected from vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tripropoxysilane, and vinyl tri(β-methoxyethoxy)silane are added to organic solvents such as ethyl acetate, butyl acetate, ethanol, and butanone and the wear-resistant inorganic material, the wear-resistant inorganic material and the organic solvent are mixed in a ratio of 2:8, and after mixing evenly, 0.5-5% of the modifier is added to the mixed solution, the solution is kept at 40-70° C. for reaction for 1-3 hours, and after the reaction is completed, the solvent in the solution is baked and volatilized to obtain the vinyl-modified wear-resistant inorganic material;
[0040] Specifically, the modification method of the epoxy-modified wear-resistant inorganic material is as follows: one or more modifiers selected from γ-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are added to organic solvents such as ethyl acetate, butyl acetate, ethanol, and butanone and the wear-resistant inorganic material, and the wear-resistant inorganic material and the organic solvent are mixed in a ratio of 2:8. After the mixture is evenly mixed, 0.5-5% of the modifier is added to the mixed solution, and the solution is kept at 40-70°C for reaction for 1-3 hours. After the reaction is completed, the solvent in the solution is baked and evaporated to obtain the epoxy-modified wear-resistant inorganic material.
[0041] Furthermore, the high water drop angle assistant includes one or a mixture of fluorine-modified acrylate, fluorine-silicon-modified acrylate, and silicone-modified acrylate, and the high water drop angle assistant contains a reactive group that reacts with a UV oligomer.
[0042] Furthermore, the photoinitiator includes one or a mixture of a free radical photoinitiator and a cationic photoinitiator, and the free radical initiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1,1'-(methylenedi-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (127), 2-methyl-1-[4-(methylthio)phenyl ]-2-(4-morpholinyl)-1-propanone (907), tetraethyl Michler's ketone (MEK); the cationic photoinitiator includes bis(4-dodecylbenzene)iodonium hexafluoroantimonate (PAG-101), diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate (6976), diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (6992), 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate (6990), and 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate (250).
[0043] In this embodiment, the method for preparing the high refractive index wear-resistant optical coating comprises the following steps:
[0044] Step 1: Add a sufficient amount of UV oligomer into a stirring barrel, and then place the stirring barrel in a stirrer for stirring, with the speed set at 800-1000 rad / min;
[0045] Step 2, add a sufficient amount of high-refractive nano inorganic material while stirring, after the addition is completed, set the stirrer to 1200-1500 rad / min and stir for 30 minutes;
[0046] Step 3, then add a sufficient amount of modified wear-resistant inorganic material while stirring, after the addition is completed, set the mixer to 1200-1500 rad / min and stir for 30 minutes;
[0047] Step 4: Grind and disperse the above-mixed product using a sand mill or a three-roll grinder, and pour the ground product into a mixing barrel and stir at 800-1000 rad / min;
[0048] Step 5: dilute the high water drop angle additive 10 times with an organic solvent such as ethyl acetate or butanone, and then add it to the mixing barrel while stirring. After the addition is completed, set the mixer to 1200-1500 rad / min and stir for 30 minutes;
[0049] Step 6: Add a sufficient amount of photoinitiator to the mixing bucket. After adding, the coating needs to be covered with a bucket cover to avoid light. Set the mixer to 1200-1500 rad / min and stir for 10 minutes.
[0050] Step 7: The stirred coating is filtered using a 0.5-1 μm filter element to obtain a high-refractive, wear-resistant optical coating.
[0051] During construction, add sufficient amount of organic solvents such as ethyl acetate, butyl acetate, butanone, methyl isobutyl ketone, etc. to dilute according to specific construction requirements.
[0052] Example 1
[0053] Raw material ratio:
[0054]
[0055] The test was carried out with 100 μm thick PET as the substrate. During the coating construction in Example 1, an ester or ketone solvent can be used to dilute the coating to a solid content of 2-6% before construction. The test results in Table 1 below are tested by diluting butyl acetate to a solid content of 3% for single-sided coating, and UV curing is performed using 700 mj / cm^2 energy. The test results are then compared with high-refractive index coatings made of domestic high-refractive resins.
[0056] Table 1. Performance comparison of high refractive index coatings prepared from Example 1 and domestic high refractive index resins
[0057] Adhesion Refractive index / % Steel wool resistant 1 / 1KG Water drop angle 2 / ° Comparative Example 1 5B 1.60 10 times, NG 78 Example 1 5B 1.64 300 times, OK 113
[0058] Note: Steel wool is 0000#, test area is 2cm*2cm, load is 1Kg, test speed is 40 times / minute, and the judgment standard is to observe the sample at a 45° angle to the light after the test, and it is OK when the number of scratches is ≤5.
[0059] The comparison results in Table 1 above show that although the refractive index of ordinary high-refractive index coatings using pure titanium dioxide can also be adjusted, there is a large gap in wear resistance compared with the high-refractive index coating provided by the present invention.
[0060] Example 2
[0061] Raw material ratio
[0062]
[0063] The test was carried out using PET with a total thickness of 55 μm and a 5 μm hardened layer as the substrate. In Example 2, the coating was diluted to a solid content of 2 to 6% using an ester or ketone solvent before construction. The test results in Table 2 below were tested by diluting butanone to a solid content of 3% for single-sided coating testing, and UV curing was performed using 800 mj / cm^2 energy. The test results were then compared with high-refractive-index coatings made in China using pure nano-titanium dioxide.
[0064] Table 2. Performance comparison of high refractive index coatings prepared from Example 2 and domestic high refractive index resins
[0065] Adhesion Refractive index / % Steel wool resistant 1 / 1KG Water drop angle 2 / ° Comparative Example 2 4B 1.65 10 times, NG 73 Example 2 5B 1.70 1000 times, OK 114
[0066] Note: Steel wool is 0000#, test area is 2cm*2cm, load is 1Kg, test speed is 40 times / minute, and the judgment standard is to observe the sample at a 45° angle to the light after the test, and it is OK when the number of scratches is ≤5.
[0067] The comparison results in Table 2 above show that although the refractive index of ordinary high-refractive-index coatings using pure titanium dioxide can also be adjusted, there is a large gap in wear resistance compared with the high-refractive-index coating provided by the present invention.
[0068] Example 3
[0069] Raw material ratio:
[0070]
[0071] The same substrate as in Example 2 was used, and PET with a total thickness of 55 μm and a hardened layer of 5 μm was used as the substrate for testing. In Example 3, the coating was diluted to 2-6% solid content using ester or ketone solvents before construction. The test results in Table 3 below were tested by diluting butanone to 3% solid content for single-sided coating testing, and UV curing was performed using 800 mj / cm^2 energy. The test results were then compared with those in Example 2 and a domestic high-refractive coating using pure nano titanium dioxide.
[0072] Table 3. Comparison of performance of high refractive index coatings prepared with Example 3, Example 2 and domestic high refractive index resins
[0073] Adhesion Refractive index / % Steel wool resistant 1 / 1KG Water drop angle 2 / ° Comparative Example 2 4B 1.65 10 times, NG 73 Example 2 5B 1.70 1000 times, OK 114 Example 3 5B 1.70 300 times, OK 76
[0074] Note: Steel wool is 0000#, test area is 2cm*2cm, load is 1Kg, test speed is 40 times / minute, and the judgment standard is to observe the sample at a 45° angle to the light after the test, and it is OK when the number of scratches is ≤5.
[0075] From the performance comparison of the high refractive index coatings of Example 2 and Example 3 in Table 3, it can be seen that the wear resistance of the formula with the addition of the water drop angle aid is significantly improved than that of the formula without the addition of the water drop angle aid; by comparing Example 3 with Comparative Example 2, it can be seen that under the same condition of not adding the water drop angle aid, the wear resistance of the coating of the present invention is still better.
[0076] In summary, the high refractive index wear-resistant optical coating provided by the present invention adopts ordinary polyurethane acrylate prepolymer with high refractive index nano-inorganic material and modified wear-resistant inorganic material to achieve the effects of high refractive index and wear resistance; by modifying the wear-resistant inorganic material so that its surface has reactive groups that can react with the polymer, the wear resistance can be improved; compared with the commonly used high refractive index coating, there is no need to use high refractive index resin as raw material, the refractive index is adjusted by nano filler, and can be freely designed within a certain range.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high refractive index wear-resistant optical coating, characterized in that: The components of the high refractive index wear-resistant optical coating are calculated by weight percentage: 40-65% UV oligomer, 15-40% high refractive index nano inorganic matter, 1-5% modified wear-resistant inorganic matter, 0-5% high water drop angle additive, and 1-6% photoinitiator.
2. A high refractive index wear-resistant optical coating according to claim 1, characterized in that: The UV oligomer includes one or a mixture of urethane acrylate oligomer, epoxy acrylate oligomer, polyester acrylate oligomer, epoxy glycidyl ether oligomer and epoxy cyclohexane oligomer.
3. The high refractive index wear-resistant optical coating according to claim 1, characterized in that: The high-refractive-index nano-inorganic material includes one or a mixture of nano-titanium dioxide, nano-silicon nitride, nano-aluminum nitride, nano-zirconium oxide, nano-silicon carbide, nano-niobium pentoxide, and nano-gallium nitride. The high-refractive-index nano-inorganic material has a refractive index of more than 2.0 and a particle size of 5 to 200 nm.
4. The high refractive index wear-resistant optical coating according to claim 1, characterized in that: The modified wear-resistant inorganic material includes a mixture of one or more of aluminum oxide, zirconium oxide, boron carbide, silicon carbide, silicon nitride, aluminum nitride, and titanium carbide. The Mohs hardness of the modified wear-resistant inorganic material is greater than 8.0, and the shape of the modified wear-resistant inorganic material is spherical or quasi-spherical.
5. The high refractive index wear-resistant optical coating according to claim 4, characterized in that: The modification process of the modified wear-resistant inorganic material is selected according to the type of UV oligomer selected. When UV oligomers containing double bonds are selected, vinyl-modified wear-resistant inorganic materials are selected. When UV oligomers containing epoxy groups are selected, epoxy-modified wear-resistant inorganic materials are selected.
6. The high refractive index wear-resistant optical coating according to claim 1, characterized in that: The high water drop angle auxiliary agent includes one or a mixture of fluorine-modified acrylate, fluorine-silicon-modified acrylate, and silicone-modified acrylate, and the high water drop angle auxiliary agent contains a reactive group that reacts with a UV oligomer.
7. The high refractive index wear-resistant optical coating according to claim 1, characterized in that: The photoinitiator comprises one or a mixture of a free radical photoinitiator and a cationic photoinitiator, wherein the free radical initiator comprises 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1,1'-(methylenedi-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (127), 2-methyl-1-[4-(methyl)-1-phenyl]-2-hydroxy-2-methyl-1-propanone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 1,1'-(methylenedi-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone] (127), The invention relates to a photoinitiator comprising: bis(4-dodecylbenzene)iodonium hexafluoroantimonate (PAG-101), diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate (6976), diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (6992), 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate (6990), and 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate (250).
8. A method for preparing a high refractive index wear-resistant optical coating as claimed in claims 1 to 7, characterized in that: The following steps are involved: Step 1: Add a sufficient amount of UV oligomer into a mixing barrel, and then place the mixing barrel in a mixer for stirring at a speed of 800-1000 rad / min. Step 2, add a sufficient amount of high-refractive nano inorganic material while stirring, after the addition is completed, set the stirrer to 1200-1500 rad / min and stir for 30 minutes; Step 3, then add a sufficient amount of modified wear-resistant inorganic material while stirring, after the addition is completed, set the mixer to 1200-1500 rpm and stir for 30 minutes; Step 4: Grind and disperse the above-mixed product using a sand mill or a three-roll grinder, and pour the ground product into a mixing barrel and stir at 800-1000 rad / min; Step 5: Dilute the high water drop angle additive 10 times with an organic solvent such as ethyl acetate or butanone, and then add it to the mixing barrel while stirring. After the addition is completed, set the mixer to 1200-1500 rad / min and stir for 30 minutes; Step 6: Add enough photoinitiator to the mixing bucket. After adding, cover the bucket with a lid to avoid light. Set the mixer to 1200-1500 rad / min and stir for 10 minutes. Step 7: Filter the stirred coating using a 0.5-1 μm filter element to obtain a high refractive index wear-resistant optical coating.
Citation Information
Patent Citations
Coating composition and coating film having enhanced abrasion resistance and fingerprint traces removability
CN101878276A
Paint composition and high-refractivity hardened layer
CN104004452A
Low-cost high-wear-resistance UV-curing coating and preparation method and application thereof
CN110684460A
Ultraviolet curing coating composition with high wear resistance and fingerprint resistance and preparation method thereof
CN111100545A
Anti-dazzle film coating liquid and anti-dazzle film
CN115594875A